Estudo de efeitos de um extrato de Arctium lappa (Bardana) na marcação dos constituintes sangüíneos com Tecnécio-99m, na biodisponibilidade do radiofármaco pertecnatato de sódio e na morfologia de hemácias de ratos Wistar - Neves, Rosane de Figueiredo (2008)
Radionuclides have been used in Nuclear Medicine for diagnostic and treatment. In basic research, cellular and molecular structures are labeled with technetium-99m (99mTc) and used as radiobiocomplexes. Some natural or synthetic drugs are capable to alter the labeling of blood constituents with 99mTc, as well as in the biodistribution of radiobiocomplexes. Arctium lappa (Bardana) has been used to treat inflammatory processes. The aim of this work was to evaluate the effects of an extract of Bardana on the labeling of blood constituents with 99mTc, on the morphology of red blood cells, on the perimeter/area ratio of red blood cells and on the biodistribution of radiophamaceutical sodium pertechnetate in Wistar rats. Extract of Bardana was capable to alter the labeling of cellular compartment with 99mTc. Plasma and cellular proteins did not present alteration on the percentage of radioactivity (%ATI). Extract of Bardana was also capable to alter the morphology and the perimeter/area ratio of red blood cells. On the biodistribution of sodium pertechnetate in animals treated with the extract of Bardana, it was observed a small and significant uptake in liver, tooth and tongue, and a high and a significant uptake in stomach, lung and testis (p<0.05). In conclusion, these findings could be justified due to the effects of some chemical compounds in the Bardana extract. This study was a multidisciplinary experimental research. It was developed with the contribution of the different Departments and Services of the Hospital Universitário Pedro Ernesto of the Universidade Estadual do Rio de Janeiro